Source Criticism and the History of Brazilian Foreign Policy - Eduardo Uziel; Norma Breda dos Santos (Contexto Internacional)
Abstract The article deals with the historical methodology in the field of Brazilian foreign policy, based on reflections on the treatment of primary sources and the lessons of two important historians of antiquity: Moses I. Finley and Arnaldo Momigliano. Without disregarding the inherent temporal differences, it is understood that it is possible to bring contemporary and ancient history closer, as well as to establish a respectful dialogue between them. The article presents a preliminary discussion on the sources for the history of Brazilian foreign policy, followed by a series of analyses and comments on several aspects of the treatment of primary sources: a) the fragmentary nature of sources and the consequences of this; b) the predominance of discursive sources; c) the use of oral history as a supplementary source; and d) the difficulty in establishing a context for document production. Studies related to Brazilian foreign policy towards the Middle East will be used, especially the case of Brazil’s controversial favourable vote on Resolution 3379 (XXX) of the United Nations General Assembly, in 1975, which equated Zionism with racism.